Agentive responsibility and possibilities of conjoined therapy for intimate relationship violence - Valkonen, Eliisa (2013)
This thesis is about how to provide conjoined therapy to couples suffering from intimate partner violence (IPV). The discourse analysis concentrated on the narrations produced in therapy and how both the therapists and customers position themselves responsibly thus with strong agency. The results suggest an array of supportive narrative practises to enhance agency and provide through psychoeducation, empowering and perspective challenging toward more individual sense of agency in speech about one’s relation to the relationship as well as to the theme of violence.